Surgical crisis management skills training and assessment: a simulation[corrected]-based approach to enhancing operating room performance. - Moorthy, K; Munz, Y; Forrest, D; Pandey, V; Undre, S; Vincent, C; Darzi, A (2006)
BACKGROUND: Intraoperative surgical crisis management is learned in an unstructured manner. In aviation, simulation training allows aircrews to coordinate and standardize recovery strategies. Our aim was to develop a surgical crisis simulation and evaluate its feasibility, realism, and validity of the measures used to assess performance. METHODS: Surgical trainees were exposed to a bleeding crisis in a simulated operating theater. Assessment of performance consisted of a trainee's technical ability to control the bleeding and of their team/human factors skills. This assessment was performed in a blinded manner by 2 surgeons and one human factors expert. Other measures consisted of time measures such as time to diagnose the bleeding (TD), inform team members (TT), achieve control (TC), and close the laceration (TL). Blood loss was used as a surrogate outcome measures. RESULTS: There were considerable variations within both senior (n = 10) and junior (n = 10) trainees for technical and team skills. However, while the senior trainees scored higher than the juniors for technical skills (P = 0.001), there were no differences in human factors skills. There were also significant differences between the 2 groups for TD (P = 0.01), TC (P = 0.001), and TL (0.001). The blood loss was higher in the junior group. CONCLUSIONS: We have described the development of a novel simulated setting for the training of crisis management skills and the variability in performance both in between and within the 2 groups.